Evolution of Urban Resilience from a Multiscale Perspective: Evidence from Five Provinces in Northwest China - Hainan Yang; Huizhen Su; Liangjie Yang (Complexity)
As a new idea of urban risk management, building resilient cities with the ability to resist, eliminate, and adapt to uncertain risks is of great importance to mitigate risk impacts and promote sustainable urban development. Based on the adaptive cycle model and the characteristics of an urban system, this study analyzes the resilience levels of cities, urban agglomerations, and provinces and their adaptive stages. The results show that (1) the comprehensive resilience of cities in the five provinces of northwest China is on the rise and that the differences between cities are gradually narrowing. The development stages of the urban adaptive cycle can be divided into six stages: the rapid exploitation stage, exploitation-conservation stage, stable conservation stage, conservation-release stage, development reorganization stage, and reorganization-exploitation stage. (2) The spatial distribution of the comprehensive resilience of urban agglomerations is “high in the southeast and low in the northwest,” and the development stage of the adaptive cycle is consistent with its central city or central region. (3) The level of resilience varies greatly among provinces, and the development stage of the adaptive cycle is equivalent to the average level of all cities in the province and is closely related to their respective development forces and urban problems. These findings can provide reference for policymakers to formulate scientific resilience building strategies to achieve regional sustainable development.